Design And Construction Of An Automatic Fish Cultivation System Based On The Internet Of Things - Ibnu Juni Saputra (Jurnal Media Computer Science, 2024)
The Internet of Things (IoT) plays a crucial role in fish farming by maintaining water quality. Government Regulation of the Republic of Indonesia No. 82/2001 sets water quality standards for fish cultivation, including a pH range of 6-9 and a temperature range of 25-32°C. Water conditions affect fish health; low temperatures reduce immunity, improper pH inhibits growth, and makes them susceptible to diseases. This research focuses on pH and temperature control using a temperature sensor on the NodeMCU ESP8266. When the sensor reads pH >9, the pump introduces pH down solution. For pH <6, the pump introduces pH up solution. The temperature sensor activates the heater below 25°C. Sensor readings are monitored in real-time through the Blynk application on Android devices. Test results demonstrate effective temperature control above 25°C and pH sensor control between 6 to 9, and resulting in optimal conditions for the fish pond water.